Knowledge Strategy: The way to Sustain Competitive Advantage for Technology-based Enterprises - Mhd Sarif, Suhaimi; Ismail, Yusof (2012)
This paper examines knowledge strategy to sustain competitive advantage for technology-based enterprises. From resource-based view, knowledge strategy enables firms to create and sustain competencies and capacity to outcompete rivals. Personal interview with 10 strategists from technology-based enterprises revealed that customized knowledge strategy is capable to create and sustain knowledge. However, the results cannot be generalized due to less rigorous qualitative analysis on the interview results. The future studies should include more informants and to use qualitative analysis software for more rigorous analysis.